Campylobacter jejuni Cytolethal Distending Toxin Induces GSDME-Dependent Pyroptosis in Colonic Epithelial Cells - Gu, Jiayun; Lin, Yan; Wang, Zhichao; Pan, Qicong; Cai, Guohua; He, Qigai; Xu, Xiaojuan; Cai, Xuwang (Frontiers in Cellular and Infection Microbiology, 2022)
Background Cytolethal distending toxin (CDT) is a critical virulence factor of Campylobacter jejuni, and it induces cell death and regulates inflammation response in human epithelial cells. Pyroptosis is an inflammatory form of programmed cell death (PCD), but whether it is involved in CDT-mediated cytotoxicity remains elusive. Aims This study explores the role and mechanism of pyroptosis in CDT-mediated cytotoxicity. Methods HCT116 and FHC cell lines were treated with CDT. Cell Counting Kit-8 (CCK-8) assay was used to detect cell viability. Western blotting was used to measure the expression of related proteins in the pathway, and cell morphology observation, annexin V/propidium iodide (PI) staining and lactate dehydrogenase (LDH) release assay were performed to evaluate the occurrence of pyroptosis. Result Our results show that C. jejuni CDT effectively induces pyroptosis in a dose- and time- dependent manner in human colonic epithelial cells owing to its DNase activity. Specific pyroptotic features including large bubbles emerging from plasma membrane and LDH release were observed upon CDT treatment. Moreover, CDT-induced pyroptosis involves the caspase-9/caspase-3 axis, which is followed by gasdermin E (GSDME) cleavage rather than gasdermin D (GSDMD). N-acetyl cysteine (NAC), a reactive oxygen species (ROS) inhibitor, attenuates the activation of caspase-9/3, the cleavage of GSDME and pyroptotic characteristic, therefore demonstrating ROS initiates pyroptotic signaling. Conclusions We first clarify a molecular mechanism that CDT induces pyroptosis via ROS/caspase-9/caspase-3/GSDME signaling. These findings provide a new insight on understanding of CDT-induced pathogenesis at the molecular level.